THE PRESSURE OF BEING HOMOSEXUALS AS REPRESENTED IN C. JAY COX’S LATTER DAYS - Oyong, Reetha Priscisla (LANTERN (Journal on English Language, Culture and Literature), 2015)
Latter Days is an American movie which can be considered as a reflection of social realitythat happens in the society nowadays. The movie showsone of social realities in this modern era which is called as sexual disorientation. Even though sexual disorientation has probably been a common issue in this era, there are still many people who consider sexual disorientation as taboo.